Sound transmission loss of a double-leaf solid-microperforated partition under normal incidence of acoustic loading - Putra, Azma; Ismail, Ahmad Yusuf; Ayob, Md Razali (2011)
One of the most considerable aspects of a vehicle design judged by the customers is the noise level inside the cabin. The conventional method is the use of absorbent materials as the noise absorber e.g. foam and other porous materials. These materials are usually made from synthetic and are therefore not environmentally friendly. Moreover, they can be easily dirty or damage and give bad odour due to smoke or moist. Since the microperforated panel (MPP) has been investigated to have a good performance as the sound absorber, there is a feasibility to implement such a panel inside a vehicle cabin. The MPP which is constructed from a solid panel will provide a hygienic and a non- abrasive material. Its optically attractive surface will also enhance the art in the cabin interior. However, the presence of holes will reduce the transmission loss performance which cannot be tolerated for a good noise barrier. This paper is the preliminary study to investigate the performance of a double-leaf solid and microperforated partition (SMPP) in terms of its sound transmission loss (STL). The mathematical model for the STL is derived. The result shows that the performance substantially improves at the troublesome frequency the so-called mass-air- mass resonance which occurs in the conventional double-leaf partition. This is important particularly for the noise source predominant at low frequencies. This can also be controlled by tuning the hole size and number as well as the air gap between the panels. However, above this frequency, the general performance of the STL is decreased.